Investigating the use of deep learning for textual entailment in BRACU-NLI dataset - Haque, Farah Binta; Yasin, MD; Saha, Shishir; Hossain, MD Mazed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.